Tanggapan Helicoverpa armigera terhadap Infeksi Subletal Nuclear Polyhedrosis Virus dan Dampaknya terhadap Laju Reproduksi - Gita Pawana; Tjandra Anggraeni; Anna Laksanawati H.D. (Jurnal Perlindungan Tanaman Indonesia, 2000)
The study on responses of Helicoverpa armigera Hbn. to sublethal HaNPV (H. armigera nuclear polyhedrosis virus) infection was carried out in the laboratory. The reproduction rate was scrutinized as their impact of HaNPVs exposures. Fifth instar of H. armigera larval was orally infected on sublethal serial dilution of HaNPV (1,800; 180; 18; 1.8; 0.18; 0.018 ppm from stock concentration of 1.1 X 10^9 PIB per ml suspension). A significantly female pupal weight forms the response of H. armigera to sublethal HaNPV infection on the concentration tested. However larval period, male pupal weight, pupal period, oviposition period, life span of imago, fecundity, fertility and survival did not significantly form the response of H. armigera to sublethal HaNPV infection. All treatment showed lower reproduction rate compared to the untreated, especially reproduction rate based on either debilitating effect and mortality or just based on debilitating effect.